Numerical investigation of an incompressible flow over a backward facing step using a unified fractional step, artificial compressibility and pressure projection (ESAC-PP) method - Jenkins, Karl W.; Teschner, Tom-Robin; Könözsy, László Z. (University of Miskolc, 2016)
This study focuses on an incompressible and laminar flow problem behind a backward facing step by employing a recently developed Fractional-Step, Artificial Compressibility and Pressure-Projection (FSAC-PP) method. The FSAC-PP approach unifies Chorin’s fully-explicit Artificial Compressibility (AC) and semiimplicit Fractional-Step Pressure-Projection (FS-PP) methods within the framework of characteristic-based (CB) Godunov-type schemes for solving the incompressible Navier-Stokes equations. The FSAC-PP approach has been originally introduced for low and moderate Reynolds number flows in conjunction with microfluidic and wide range of multiphysics applications. In this work, we demonstrate the applicability of the novel FSAC-PP method to macro-scale separated flows at a moderate Reynolds number. The computational results obtained with the FSAC-PP approach have been compared to the AC method and experimental data to highlight its favorable accuracy and convergence properties for separated flows.